Предмет: Алгебра,
автор: MikaKamila
Помогите пожалуйста :))
Приложения:
Ответы
Автор ответа:
0
(a+x)³ - a(a+x)² -x²(2a+X) =a³ +3a²x +3ax²+x³ -a(a²+2ax+x²) -2ax² -x³ =
a³ +3a²x +3ax² -a(a²+2ax+x²) -2ax²=a³ +3a²x +3ax² -a³-2a²x-ax² -2ax² =a²x .
---
a³ +3a²x +3ax² -a(a²+2ax+x²) -2ax²=a³ +3a²x +3ax² -a³-2a²x-ax² -2ax² =a²x .
---
Автор ответа:
0
3ax²- ax² -2ax² =0 ; a³- a³=0 ; 3ax²- 2ax² =ax²
Похожие вопросы
Предмет: Қазақ тiлi,
автор: WI12
Предмет: Литература,
автор: Rerthhy6
Предмет: Английский язык,
автор: turdalievanazik64
Предмет: Математика,
автор: Lisiania
Предмет: Математика,
автор: Аноним